Assessment of anxiety and depression status among health care workers from Baghdad post cure from COVID-19 - Mohammed, Iman Ahmed; Hamdan, AbdulGhani Sadoon; Jaber, Osamah Abbas; Abbas, Ghsoon Harbi (Journal of the Faculty of Medicine Baghdad, 2021)
BACKGROUND: A novel coronavirus officially recognized as SARS-CoV2, first emerged in Wuhan, China, has allowed COVID-19 to rapidly spread. The WHO declared the global pandemic of COVID-19 a public health emergency of international concern. Early evaluation of the mental health of healthcare workers (HCWs) and consideration of effective therapeutic strategies is important. OBJECTIVE: To assess the mental status (depression and anxiety) among HCWs and identify the association between depression, anxiety levels and (certain demographic factors and other factors).PATIENTS AND METHODS: A cross-sectional study was conducted on data collected from 11th-17th Jan 2021 by an electronic questionnaire. All HCWs of all age groups working at health facilities belong to Al-Resafa health directorate diagnosed as COVID-19 and then get cured were included.RESULTS: The mean age ± SD of the HCWs = 35.5±9.9 yrs., 61.0% females. Regarding depression 29.7% of HCWs were normal and 43.2% their anxiety level was normal. Depression and anxiety were statistically significantly associated with institution type, gender, job title, smoking status, hospital admission, oxygen use, O2 saturation level